Perlindungan Hak Layanan Kesehatan Ibu Bersalin di Rumah Sakit Umum Daerah Kabupaten Kepulauan Mentawai - Sinabariba, Marita Ronitua (Journal of Global Legal Review, 2023)
The degree of public health in a country is influenced by the existence of health facilities. Law of the Republic of Indonesia Number 17 of 2023 concerning Health states that health service facilities are places and/or tools used to provide health services to individuals or communities using promotive, preventive, curative, rehabilitative and/or palliative approaches carried out by the Government. Central, Regional Government, and/or the community. The health facilities in question consist of health service facilities, pharmaceutical facilities and medical equipment, as well as government-owned health education institutions that produce health workers. In Indonesia, protecting the right to health services is part of the implementation of health efforts as regulated by Law Number 17 of 2023 concerning Health. Therefore, maternal health services have become an inseparable part of the state's guarantee of the right to health. Even though this law is still relatively new, this and existing legal products do not yet regulate the rights to health services for birthing mothers specifically and comprehensively. The research method used is normative law by studying several things such as legal principles, document studies, and using various secondary data such as statutory regulations, court decisions, legal theory, and can be the opinions of scholars. Seeing the importance of protecting the right to health services for mothers who are giving birth, the author sees that the Law of the Republic of Indonesia Number 17 of 2023 concerning Health does not specifically have any special provisions for protecting the rights of mothers who are giving birth to get health services so this research will have the aim of the birth of the Law. Law of the Republic of Indonesia Number 17 of 2023 concerning Health provides protection for the right to good health services for mothers giving birth in health facilities in general and at the Mentawai Islands District General Hospital in particular.